Wireless Interconnect in Multilayer Chip-Area-Networks for Future Multimaterial High-Speed Systems Design. (5th December 2017) - John Famoriji, Oluwole; Yan, Xu; Khan, Mehdi; Kashif, Rao; Fadamiro, Akinwale; Ali, Md Sadek; Lin, Fujiang
Abstract : Wireless chip area network which enables wireless communication among chips fosters development in wireless communication and it is envisioned that future hardware system and developmental functionality will require multimaterial. However, the traditional system architecture is limited by channel bandwidth-limited interfaces, throughput, delay, and power consumption and as a result limits the efficiency and system performance. Wireless interconnect has been proposed to overcome scalability and performance limitations of multihop wired architectures. Characterization and modeling of channel become more important for specification of choice of modulation or demodulation techniques, channel bandwidths, and other mitigation techniques for channel distortion and interference such as equalization. This paper presents an analytical channel model for characterization, modeling, and analysis of wireless chip-to-chip or interchip interconnects in wireless chip area network with a particular focus on large-scale analysis. The proposed model accounts for both static and dynamic channel losses/attenuation in high-speed systems. Simulation and evaluation of the model with experimental data conducted in a computer desktop casing depict that proposed model matched measurement data very closely. The transmission of EM waves via a medium introduces molecular absorption due to various molecules within the material substance. This model is a representative of channel loss profile in wireless chip-area-network communication and good for future electronic circuits and high-speed systems design.